Immunovirotherapy: The role of antibody based therapeutics combination with oncolytic viruses - Jafari, Mahdie; Kadkhodazadeh, Maryam; Shapourabadi, Mina Bahrololoumi; Goradel, Nasser Hashemi; Shokrgozar, Mohammad Ali; Arashkia, Arash; Abdoli, Shahriyar; Sharifzadeh, Zahra (Frontiers in Immunology, 2022)
Despite the fact that the new drugs and targeted therapies have been approved for cancer therapy during the past 30 years, the majority of cancer types are still remain challenging to be treated. Due to the tumor heterogeneity, immune system evasion and the complex interaction between the tumor microenvironment and immune cells, the great majority of malignancies need multimodal therapy. Unfortunately, tumors frequently develop treatment resistance, so it is important to have a variety of therapeutic choices available for the treatment of neoplastic diseases. Immunotherapy has lately shown clinical responses in malignancies with unfavorable outcomes. Oncolytic virus (OV) immunotherapy is a cancer treatment strategy that employs naturally occurring or genetically-modified viruses that multiply preferentially within cancer cells. OVs have the ability to not only induce oncolysis but also activate cells of the immune system, which in turn activates innate and adaptive anticancer responses. Despite the fact that OVs were translated into clinical trials, with T-VECs receiving FDA approval for melanoma, their use in fighting cancer faced some challenges, including off-target side effects, immune system clearance, non-specific uptake, and intratumoral spread of OVs in solid tumors. Although various strategies have been used to overcome the challenges, these strategies have not provided promising outcomes in monotherapy with OVs. In this situation, it is increasingly common to use rational combinations of immunotherapies to improve patient benefit. With the development of other aspects of cancer immunotherapy strategies, combinational therapy has been proposed to improve the anti-tumor activities of OVs. In this regard, OVs were combined with other biotherapeutic platforms, including various forms of antibodies, nanobodies, chimeric antigen receptor (CAR) T cells, and dendritic cells, to reduce the side effects of OVs and enhance their efficacy. This article reviews the promising outcomes of OVs in cancer therapy, the challenges OVs face and solutions, and their combination with other biotherapeutic agents.